ITINERANT CURRICULUM THEORY: TOWARDS A JUST PEDAGOGY - Janson, Elizabeth (Revista Teias, 2019)
Abstract: In this article, I examine how Joao Paraskeva’s Curriculum Epistemologies deepens his previous work on Itinerant Curriculum Theory (ICT) and discuss how this can be seen within the US public education classroom. I analyze (a) how the intricacies of ICT allow educators to fight for a just pedagogy by creating spaces of empowerment for youth and decolonizing the Curriculum; (b) how the standardization of US curriculum can be seen as an anti-ICT which helps teachers theorize spaces for ICT. This analysis of ICT reflects the need to struggle for social and cognitive justice through a just pedagogy of hope.